EXPLORATION, ISOLATION, PHENOTYPICAL, & BIOCHEMICAL CHARACTERIZATION OF INDIGENOUS METALLOTOLERANT BACTERIAL ISOLATES FROM HATTAR INDUSTRIAL ESTATE, HARIPUR: TOWARDS ENVIRONMENTAL REMEDIATION AND SUSTAINABLE INDUSTRIAL PRACTICES - Ayisha Bibi; Abdul Ghafar Khan; Sumaira Noor; Sadia Ikram; Saima Inam; Syed Zeeshan Haider; Attiq Ullah; Sania Javed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study addresses heavy metal contamination in Hattar Industrial Estate, Haripur, Pakistan, emphasizing the global issue of environmental pollution. The research focuses on isolating and characterizing metallotolerant bacterial strains from the contaminated soil, aiming to contribute to sustainable industrial practices and environmental health. Soil samples from Hattar Industrial Estate were collected and metallotolerant bacteria were isolated using a serial dilution method. two strains (Strain A, Strain B) were selected for further analysis based on their resistance to heavy metals. Morphological and biochemical characterization, including catalase, citrate, indole, urease, coagulase, and oxidase tests, were performed to understand the strains' traits and metabolic capabilities. The isolated strains, identified as Kingella sp., Listeria sp., demonstrated distinct morphological characteristics. Biochemical tests revealed variations in catalase, citrate utilization, indole production, urease activity, coagulase reaction, and oxidase activity among the strains. The results indicated the strains' potential for biological remediation, with specific resistance to heavy metals. The study underscores the importance of bioremediation as an eco-friendly approach to mitigate heavy metal contamination. The isolated bacterial strains, resistant to various heavy metals, hold promise for sustainable remediation strategies. The research advocates for the application of these strains in addressing heavy metal pollution, contributing to environmental sustainability, and promoting eco-friendly practices in industrial areas.